Hoarseness after tracheal intubation - Martins, Regina Helena Garcia [UNESP] (2006)
BACKGROUND AND OBJECTIVES: To describe the main causes of hoarseness after undergoing tracheal intubation. CONTENTS: Hoarseness is one of the most common postoperatory symptoms after tracheal intubation and the effects vary in terms of duration, depending on the factors that caused it and on how severe the damage to the laryngeal structures. This study performed a brief check-up of the anatomical structures of the larynx, describing the main traumatic lesions in the region following tracheal intubation. It also emphasized the importance of caring for the larynx, as well as undergoing early diagnosis and treatment. CONCLUSIONS: Traumatic lesions of the laryngeal structures that occur during intubation are the most common causes of hoarseness. As such, it is important to perform an early diagnosis and adopt preventive measures. © Sociedade Brasileira de Anestesiologia, 2006.